An innovative approach of blending security features in energy-efficient routing for a crowded network of wireless sensors - Pathan, Al-Sakib Khan; Ahmed, Tarem (CRC Press, Taylor & Francis Group, USA, 2014)
Wireless sensor networks (WSN) are emerging as both an important new tier in the IT (information technology) ecosystem and a rich domain of active research involving hardware and system design, networking, distributed algorithms, programming models, data management, security, and social factors [1,2]. The basic idea of a sensor network is to disperse tiny sensing devices over a specific target area. These devices are capable of sensing certain changes of incidents or parameters and of communicating with other devices. WSNs could be very useful for providing support for some specific purposes, such as target tracking, surveillance, environmental monitoring, etc. Today’s sensors can monitor temperature, pressure, humidity, soil makeup, vehicular movement, noise levels, lighting conditions, the presence or absence of certain kinds of objects or substances, mechanical stress levels on attached objects, and other properties. As such types of networks are composed of resource-constrained tiny sensor nodes, many research works have tried to focus on efficient use of the available resources of the sensors. Energy is, in fact, one of the most critical factors that play a great role to define the duration of an active and operable network. Energy efficiency is often very crucial in these sorts of networks as the power sources of the inexpensive sensors are (in most of the cases) not replaceable after deployment. If any intermediate node between any two communicating nodes runs out of battery power, the link between the end nodes is eventually broken. So any protocol should ensure a competent way of utilizing the energies of the sensors so that a fair connectivity of the network could be ensured throughout its operation time. Energy efficiency is also very necessary to maximize the lifetime of the network.